Analisa Statigrafi Seismik Dalam Menentukan Play Hidrokarbon Dengan Menggunakan Diagram Wheeler - Indah Gumilang Dwinanda (Gravity : Jurnal Ilmiah Penelitian dan Pembelajaran Fisika, 2023)
Seismic stratigraphy is one of the efforts in interpreting stratigraphy from seismic data. In seismic data, things that can be construed include faults, facies, depositional environments, sequence boundaries, petroleum systems, etc. Studies related to seismic stratigraphy are an essential part of oil and gas exploration activities. These studies can support the analysis of results in early fields with minimal data or fields without good data. The results of stratigraphic analyses on subsequent seismic data are useful as a basis for further exploration activities. A simple method that can be used to interpret seismic data is by using a wheeler diagram. The interpretation results obtained from stratigraphic analysis on seismic data with a width of 5 Km and a depth of 50 ms are ten faults with a descending pattern, and there are five sequence boundaries based on the continuity pattern of seismic data. Based on the results of stratigraphic interpretation on seismic data, the reservoir deposition environment is in the transition area. The petroleum system that can be indicated from the seismic data is that the reservoir is in the off-lap section and also in the basin floor fan, the source rock is below the reservoir zone, the reservoir migration pattern passes through the fault, and the shale at the top of the reservoir layer can be a seal rock and the trapping pattern in the seismic data is generally a stratigraphy trap